The Influence of Workload and Job Stress on Employee Quit Intentions at CV Premium Indonesia - Figo Afriansyah; Mei Retno Adiwaty (Digital Innovation : International Journal of Management, 2026)
This study aims to analyze the employee turnover rate experienced by CV Premium Indonesia employees through the influence of workload and job stress. As a company engaged in the retail and distribution of mobile phone accessories from leading brands, the desire to leave the company often arises due to high workload and feelings of work stress because of the many demands within the company. The methodology used in this study is quantitative, employing SEM model data analysis with the help of SmartPLS software. The sampling technique used is saturated sampling, with a total sample of 127 respondents. The results of this study indicate that high levels of workload can increase employee turnover rates. Meanwhile, high levels of job stress experienced by employees can also increase employee turnover rates. These findings suggest that CV Premium Indonesia should address the issues of workload and job stress in order to retain employees. Effective strategies such as work-life balance, stress management programs, and workload adjustments could help reduce employee turnover and improve overall organizational performance.